The Impact of CEO Turnover on Stock Volatility - Gooding, Khiam (2015)
This paper seeks to investigate the causal relationship between CEO turnover and stock volatility. Given that CEO turnover is often cited as one of the major internal changes faced by companies, I assess how this event affects the level of risk associated with the firm by measuring the change in volatility from one year prior to turnover to one year post-turnover. This paper makes use of propensity score matching which reduces the sample selection bias inherent in such causal studies where firms are not chosen at random. It further applies a difference-in-difference estimator in order to measure the effects of the CEO turnover on volatility. Three hypotheses were tested in this paper. The strategy and ability hypotheses suggest that stock volatility would increase following CEO turnover while the scapegoat hypothesis however, holds that there would be no change in volatility post CEO turnover. I find evidence only of the scapegoat hypothesis, which suggests that most of the turnover events are an exercise in reputation management, especially with more scrutiny placed on boards post-Sarbanes-Oxley act, to be vigilant over managers of the firm. This leads to boards replacing CEOs when performance is below expectations due to factors beyond the CEO’s control. CEOs are replaced with others who are equally as skilled which is suggested to have long-term negative effects for the company; such effects may not be captured by the volatility measure used in this research.